Elimination:
3x - 9y = 3
6x - 3y = -24
3x - 9y = 3
18x - 9y = -72
(subtract)
-15x = 75
÷ -15
x = -5
(3 × -5) - 9y = 3
-15 - 9y = 3
+ 15
-9y = 18
÷ -9
y = -2
Substitution:
6x - 3y = -24
+ 3y
6x = -24 + 3y
÷ 6
x = 4 + 0.5y
3(4 + 0.5y) - 9y = 3
12 + 1.5y - 9y = 3
12 - 7.5y = 3
- 12
-7.5y = -9
÷ -7.5
y = 1.2
x = 4 + (0.5 × 1.2)
x = 4 + 0.6
x = 4.6
So this one didn't fail as much, but I got different numbers. If you have to give in values, I'd give in the values from the elimination because I don't trust myself when it comes to the substitution
Answer:
The radius is 18 cm
Step-by-step explanation:
The formula for circumference with radius is
C = 2*pi*r
We know the circumference is 36 pi
36 pi = 2 * pi *r
Divide by pi
36 pi/pi = 2 * pi/pi *r
36 = 2r
Divide by 2
36/2 = 2r/2
18 = r
Answer:
u <= 80
u > 80
Step-by-step explanation:
The happiest would be
Null hypothesis: u <= 80
Alternative hypothesis: u > 80
B. 10, C. 4.9, D. 5.1, E. 5